Pediatric Oral/Maxillofacial Soft Tissue Sarcomas: A Clinicopathologic Report of Four Cases - Joel C. Thompson; Gary M. Woods; Michael A. Arnold; Charles Elmaraghy; Samir B. Kahwash; Timothy P. Cripe; Bhuvana A. Setty (Case Reports in Oncology, 2016)
Pediatric soft tissue sarcomas of the oral/maxillofacial region are rare neoplasms that present significant difficulty with respect to treatment and local control measures. We report four cases of pediatric oral/maxillofacial soft tissue sarcomas from our tertiary care pediatric hospital and emphasize the rarity of these malignancies and the challenges encountered in treating these lesions, and suggest areas for further research. We conclude that multimodal therapy and interdisciplinary cooperation are paramount to successful management of these lesions.